Effectiveness Analysis of Oversampling Techniques By The Lens of Item Response Theory - Corrêa, Fabrício E.; Cardoso, Lucas F. F.; Santos, Vitor C. A.; Francês, Regiane S. Kawasaki; Alves, Ronnie C. O. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2024)
It is increasingly common for sectors of society to use Machine Learning (ML) techniques to make decisions and make variations with the data generated. One of the most common problems that a dataset can present is imbalance. Under these conditions, the tendency is to produce biased models, which favor the majority class. To mitigate this problem, data balancing algorithms can be used, one of which is oversampling. However, it is not a simple task to define whether an oversampling technique really helps in the model learning process. The experiments carried out show that IRT is capable of revealing the impact of oversampling even when there is no variation in performance when using classical characteristics. Furthermore, the results found pointed to the existence of an imbalance threshold where oversampling techniques are more effective.